Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jobcr.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Glandular odontogenic cyst – Literature review and report of a paediatric case

Abstract: Glandular odontogenic cyst (GOC) is an extremely rare lesion occurring in the jawbones. The present paper is a review of 181 cases of GOCs reported in English literature, since it was first reported by Padayache and Van Wyk in 1987. Mandible was involved in 130 cases and maxilla in 51 cases. Anterior mandible was the most common area of involvement. Radiographic appearance was that of a unilocular radiolucency in 98 of 176 reported cases. Rest presented as multilocular radiolucency. Cortical expansion was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 21 publications
(11 reference statements)
0
33
1
8
Order By: Relevance
“…The treatment modalities of GOC include enucleation with or without curettage, marsupialization, peripheral ostectomy, chemical cauterization with carnoy's solution, and marginal or segmental resection . Nevertheless, conservative surgical approach such as enucleation with or without curettage and peripheral ostectomy are the commonest treatment modalities reported in the literature . Due to its tendency to recur after conservative surgical approach, some authors prefer marginal resection and segmental resection especially in larger lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment modalities of GOC include enucleation with or without curettage, marsupialization, peripheral ostectomy, chemical cauterization with carnoy's solution, and marginal or segmental resection . Nevertheless, conservative surgical approach such as enucleation with or without curettage and peripheral ostectomy are the commonest treatment modalities reported in the literature . Due to its tendency to recur after conservative surgical approach, some authors prefer marginal resection and segmental resection especially in larger lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Glandular odontogenic cyst (GOC) is an uncommon odontogenic cyst with an incidence of 0.12-0.2% of odontogenic cysts (1)(2)(3). The histological criteria for GOC have evolved since it was first described by Gardner et al in 1988 and its diagnosis is less of a challenge today in light of an increasing number of reports and clearer definition of its diagnostic criteria (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The histological criteria for GOC have evolved since it was first described by Gardner et al in 1988 and its diagnosis is less of a challenge today in light of an increasing number of reports and clearer definition of its diagnostic criteria (2,4,5). GOC has been traditionally described as predominantly affecting middle-aged individuals in their 4th-7th decades of life (mean=45.9 years-old) (2,3). While some studies report no significant gender predilection (1,3,(6)(7)(8), others have reported a slight male predominance of 1.3:1 to 2:1 (2,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations